Reaktualisasi Tradisi Menuju Transformasi Sosial: Studi Pemikiran Muhammad Abid Al-Jabiri - Happy Saputra (Fakultas Ushuluddin dan Filsafat UIN Ar-raniry Banda Aceh, 2016)
The idea of Muhammad 'Abid Al-Jabir on tradition (turats) cannot be separated from the project thought he called the Critique of the Arab Reasoning. This criticism was driven by the spirit of revivalism (Islamic Awakening) which is divided into two ideas as a reflection of the Islamic awakening failures and an effort to actualize social transformation. Al-Jabiri considers Islamic Awakening in this modern era has not been successful or even fail. One of the fundamental causes of such failure is imprecision in dealing with tradition. According to him, tradition is something from the past that exists and accompanies our present. It may be our past or the past of others. The past may be close or far. Al-Jabiri further suggests that existing traditions are deeply rooted in Islamic thoughts developed by the scholars from the second century of Hijrah to about eight centuries of Hijriah. In its essence, these traditions are related to aspects of thought in Islamic civilization, ranging from doctrinal teachings, the Shari'ah, language, literature, art, theology, and Sufism. Thus, it is not a surprise that Al-Jabiri later focused on written Islamic traditions to be dismantled and understood objectively. His views aim to foster viability of Islamic awakening and achieve social transformation.